2006
DOI: 10.1038/nature04628
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interference between two single photons emitted by independently trapped atoms

Abstract: When two indistinguishable single photons are fed into the two input ports of a beam splitter, the photons will coalesce and leave together from the same output port. This is a quantum interference effect, which occurs because two possible paths-in which the photons leave by different output ports-interfere destructively. This effect was first observed in parametric downconversion (in which a nonlinear crystal splits a single photon into two photons of lower energy), then from two separate downconversion cryst… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
269
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(275 citation statements)
references
References 22 publications
6
269
0
Order By: Relevance
“…These results demonstrate that the solid-state pulsed RF single photons in quick succession are highly indistinguishable to a level comparable to the best results from those welldeveloped systems such as parametric down-conversion [1], trapped atoms and ions [41][42][43][44]. The high-visibility results indicate a reduction of the fast dephasing and an elimination of the emission time jitter associated with the pulsed RF, compared to the previous incoherent excitation methods.…”
Section: Two-photon Quantum Interferencesupporting
confidence: 69%
“…These results demonstrate that the solid-state pulsed RF single photons in quick succession are highly indistinguishable to a level comparable to the best results from those welldeveloped systems such as parametric down-conversion [1], trapped atoms and ions [41][42][43][44]. The high-visibility results indicate a reduction of the fast dephasing and an elimination of the emission time jitter associated with the pulsed RF, compared to the previous incoherent excitation methods.…”
Section: Two-photon Quantum Interferencesupporting
confidence: 69%
“…In the same way, sub-Rayleigh resolution enhanced by a factor of four is obtained for N = 4 emitters and using N = 4 detectors. By extending this scheme, we show that the same results are also obtained for different objects, e.g., in case of a grating with N slits.Only recently, first experiments were able to observe higher order interferences of photons emitted by single trapped atoms [15,16,17,18]. These observations stand in a long line of experiments using single photon sources to investigate interference phenomena of single-and multi-photon amplitudes.…”
mentioning
confidence: 99%
“…In the well-known Hong-OuMandel (HOM) interference [3,4], it was found that two identical photons coalesce in the BS and go together into the same output port. This two-photon quantum interference effect has been confirmed from paired photons in spontaneous parametric down-conversion [3], four-wave mixing [5], and single photons from independent sources [6,7]. In these experiments, the indistinguishability between the two photons is the key for observing the HOM effect where the detectors are slow as compared to the bandwidth of the photons.…”
mentioning
confidence: 88%